Penataan Arsip Desa Di Desa Kageroa Kecamatan Lore Barat Kabupaten Poso - Margaretha Badu; Galip Lahada (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The Arrangement of Village Archive purposes is to provide understanding and skills to village officials in Kageroa village, Lore Barat Sub-district in carrying out archival activities. This training activity is beneficial for the village government in realizing the implementation of village governance in a good and orderly manner. The targets of activity are the Village Secretary, Head of Government Affairs, Head of Development Affairs, Head of General Affairs and Head of Financial Affairs in Lore Barat Sub District. However, in this case, the arrangement of village archives in Lore Barat Sub District, Poso Regency is not optimal or still not good because it is not as expected, namely the archives are still messy or not well organized with the system used, so that archiving activities do not run well in archive storage and retrieval. This is due to the lack of responsibility of the employee in other words every archive is not stored in an orderly and orderly manner based on the system, so that in storage, archives are not easily and quickly recovered. Therefore, we suggest that it is necessary to improve the understanding of village officials by providing technical guidance on archive management. In addition, increasing awareness of village officials on the importance of archives to realize good and orderly village governance. Archives can provide information to the maximum, it is necessary to manage archives properly and regularly and every employee or archive processor must be given training, education, courses, directions, guidance on archive management. well in improving administrative order.